Pengaruh Metode Kuis Menggunakan Aplikasi Quizizz dan Ice Braking Terhadap Motivasi Belajar pada Materi Sistem Persamaan Linear Tiga Variabel - Nur Hasanah; Ida Fitriana Ambarsari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Learning is a process for someone to get a certain skill or competency achievement in accordance with their respective abilities, each student requires a process with different levels of ability. Good learning is learning that has been well planned and structured, in making a learning plan the teacher needs to see the abilities of each student so that the designed learning runs well. This study examines the effect of Ice Breaking and Quizizz on learning motivation, which has a strong relationship. For the results of the multiple regression test obtainedvalue Sig. For the variable capita selecta on learning motivation of 0.009> 0.05 and the value of t count 4.179 > t table 2,228, so it can be concluded that there is a significant effect. It is found that the significant value of the variable is 0.895>0.005 and the t-count value is 0.138 <2.228 so it can be concluded that there is no significant effectso that there is a relationship but not necessarily a significant influence